The Cultural Identity of the Main Character of the Film Green Book - Syarif Hidayat; Ledya Juliandina; Rusydi M. Yusuf (Pioneer: Journal of Language and Literature, 2022)
Being an African-American in the United States of America is challenging due to the persistent racism in that country. One of the worst effects of racism is losing someone’s identity. Despite their best efforts, African Americans still struggle to fit into American culture and find acceptance. This study was conducted because of this issue. This research is entitled “The Cultural Identity Analysis of the Main Character “Don Shirley” in the film Green Book”. This study aims to learn more about Don Shirley's struggles with cultural identity and his eventual identity negotiation. This descriptive qualitative research was conducted using Stuart Hall’s theory of identity. This research reveals that Don Shirley initially adopts the identity of a white-cultured guy due to the influence of racism on his thoughts, words, and actions. However, this does not guarantee his acceptance by society. Therefore, he finally embraces himself and negotiates his African-American identity.